PENGARUH STRUKTUR AKTIVA, UKURAN PERUSAHAAN, PELUANG BERTUMBUH DAN PROFITABLITAS TERHADAP STRUKTUR MODAL (Studi Pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia) - Damayanti, Damayanti (JURNAL PERSPEKTIF BISNIS, 2013)
Every company needs a source of funding for operational activities of the company.Â  Source of funds can be obtained from internal sources (retained earnings) and can be from external companies, ie loans, so that company must determine the right composistion of capital structure from the various funding sources.Â  In determining the appropriate capital structure, the company must consider several factors from the characteristic of the company, such as asset structur, firm size, growth opportunities and company profitability.By using multiple regression analysisi with SPSS software, this study aims to determine influence both simultaneously and partially of assets structure, firm size, growth opportunity and profitability on the capital structure in the pharmaceutical companies listed on the Indonesian Stock Exchange.The result showed that there was a good influence both simultaneously and partially between asset structure, firm size, growth opportunities and profitability on the capital structure.Keyword: asset structure, firm size, growth, profitability , capital structure